Le carte del monastero di S. Maria di Chiaravalle milanese. Additiones documentarie (secolo XII) - Piva, Maria Cristina; Salemme, Timothy (Scrineum, 2013)
Founded in 1135 in the immediate outskirts of Milan, Cistercian monastery of S. Maria di Chiaravalle was one of the most important ecclesiastical institutions in Lombardy. Since its foundation, it has played a prominent role in the political, religious, social and economic life of the city. In the Middle Ages the abbey distinguished itself with intensive production and preservation of documents, exemplified nowadays by the several hundreds of charterse preserved in the Archivio di Stato of Milan. This research aims to complete the organic reconstruction work, recently carried out by Anna Maria Rapetti and Ada Grossi regarding the XII century tabularium of Chiaravalle, with the critical edition of 28 unreleased documents dated between 1106 and 1164. In the introduction, in addition to the presentation of the documents, a paragraph will outline the historiographical balance of the studies conducted so far on the abbey.